Effect of delays in primary care referral on survival of women with epithelial ovarian cancer: retrospective audit - Kirwan, John M J (BMJ, 2002)
OBJECTIVE: To examine referral pathways from primary care for patients with epithelial ovarian cancer and to identify factors related to survival at 18 months. DESIGN: Retrospective review of patient notes. SETTING: General practices and receiving hospitals within Mersey region. SUBJECTS: 135 patients with epithelial ovarian cancer identified from an audit in the Mersey area between 1992 and 1994. MAIN OUTCOME MEASURES: Delays between onset of symptoms and treatment attributable to patient, general practitioner, and hospital. RESULTS: 105 (78%) women first presented to their general practitioner within four weeks of the onset of symptoms. 99 (73%) women were referred to hospital by their general practitioners within four weeks of presentation, and 95 (70%) were seen in hospital within two weeks of referral. Multivariate analysis with survival as the dependent variable identified age (odds ratio 0.96, 95% confidence interval 0.93 to 0.99) cancer stage III or more (0.15, 0.05 to 0.43), and non-specific symptoms (0.36, 0.14 to 0.89) as significant variables. CONCLUSION: Most patients attended their general practitioner within four weeks and were referred within two weeks. No evidence was found that delays in referral or diagnosis adversely affected survival at 18 months. Stage of disease at surgery was the most important adverse factor. An effective screening programme is the most likely method to improve survival.